The Influence Of Viral Marketing On Instagram Application Users' Purchase Intention @Kopikenangan.Id - M Widyadhana Putra Nadhindra; Anas Hidayat (Cita konsultindo, 2025)
This study aims to examine the influence of viral marketing on the purchase intention of Instagram application users @Kopikenangan.id. The research method used is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. Quantitative data were collected through questionnaires completed by 300 respondents and analyzed using SmartPLS software. The results of the structural model analysis show that the quantity and credibility of information conveyed through viral marketing have a positive and significant impact on the usefulness of information. Furthermore, the usefulness of this information also positively and significantly affects the ease of information, which ultimately enhances consumer purchase intention. All hypotheses tested in this study were accepted, with T-statistic values > 1.96 and P-values < 0.05, indicating strong statistical support for the proposed model. This study provides valuable insights into how elements of viral marketing can influence consumer purchasing decisions. These findings can be utilized by marketing teams to design more effective communication strategies on social media, thereby increasing consumer engagement and purchase intention toward the offered products. By understanding these dynamics, companies can optimize viral marketing campaigns to achieve better results in terms of sales and consumer loyalty.